ILEUS OBSTRUCTION, DIAGNOSIS AND MANAGEMENT - Novi Indrayani, Margaretha (E-Jurnal Medika Udayana; vol 2 no4 (2013):e-jurnal medika udayana, 2013)
Obstructive ileus or also called mechanical ileus is a condition in which the contents of the lumen of the gastrointestinal tract can not be distributed to the distal or anus. Strangulated hernia is one of the emergencies that are often encountered by surgeons and is the biggest cause of intestinal obstruction. Common symptoms such as shock, oliguric and electrolyte disturbances. Furthermore, excess fluid was found meteorismus and intestines, such as periodic hiperperistaltis colic accompanied by nausea and vomiting. The main objective of management is part of the obstructed decompression to prevent perforation. Surgery is usually required. Eliminate the cause of obstruction is the second objective.
Keywords: Ileus obstructive